CONVERGENCE OF HEALTH EXPENDITURE IN EU 12 AND V4 STATES - Kułyk, Piotr; Augustowski, Łukasz (Copernican Journal of Finance & Accounting, 2017)
The subject of this paper is an attempt to assess the level of convergence of government health spending in the European Union countries. The ever-increasing level of life expectancy, demographic changes, including the aging of society in many European countries, and the development of medical technologies are a growing challenge for modern nations. The similarities in the changes taking place in the EU states lead to considering whether there are similar transformations in health spending? Ensuring access to primary healthcare is one of the tasks of the welfare state and it can be assumed to be a public good. Accepting these reasons, the authors set out to investigate the phenomenon of sigma and beta unconditional convergence for the level of government spending on health care in the EU countries. The answer to the question has been sought: does participation in the EU leads to convergence in government spending on health care? The study uses selected dispersion measures for sigma convergence calculations and econometric modelling for beta convergence.